PENGARUH MOTIVASI KERJA DAN IKLIM KERJA TERHADAP KINERJA KARYAWAN PADA BADAN PENGUSAHAAN KAWASAN PERDAGANGAN BEBAS DAN PELABUHAN BEBAS SABANG (BPKS) DI KOTA SABANG - Saputra, Asmara Diah; Purba, Saut; Sembiring, Rasmulia (JURNAL PROINTEGRITA, 2020)
This study aims at determining the effect of partially and simultaneously motivation and work climate on the performance of employees in the Free Trade Zone and Sabang Free Ports. This research was conducted at the Free Trade Zone and Port of Sabang Free Trade Agencies (BPKS) in August - September 2018. Based on the Slovin formula the number of samples in this study is 57 people. The independent variable consists of work motivation (X1) and work climate (X2), while the dependent variable is employee performance (Y). Data analysis was performed using multiple linear regression analysis. The results showed that motivation partially had a significant effect on the performance of employees at the Free Trade Zone and Sabang Free Port Management Agency with a tvalue of 6.634> ttable 1.670. The work climate partially has a significant effect on the performance of employees at the Free Trade Zone and Sabang Free Port Concession Agency with a tvalue of 2.573> ttable 1.670. Work motivation and work climate simultaneously have a significant effect on the performance of employees at the Free Trade Zone and Sabang Free Port Management Agency with an Fcount of 26.375> Ftable 3.17.